CaO Berbasis Kulit Telur Ayam Dengan Penambahan Karbon Aktif Dan Natrium Hidroksida (CaO-NaO/C) Sebagai Katalis Untuk Sintesis Biodiesel Dari Minyak Sawit Off-Grade - Rahayu, Ricky Puji; Helwani, Zuchra; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Chicken eggshells CaO based catalyst with the addition of activated carbon and sodium hydroxide (CaO-NaO/C) has been successfully synthesized for production of biodiesel from palm oil off-grade. The catalyst was characterized by X-Ray Diffraction analysis (XRD), Brunauer-Emmett-Teller (BET) and basic strength while the characterization of biodieselwas by Gas Chromatography-Mass Spectrometry (GC-MS). The catalyst was synthesized by calcining the chicken eggshell as source of CaCO3 at the calcination temperature of 900 ˚C for 3 hours. The CaO was then supported by activated carbon as catalyst buffer andimpregnated with 30% NaOH solution. The catalyst with the highest catalytic activity was obtained at calcination temperature of 500 ˚C and mass ratio of CaO:C at 6:4. The yield of biodiesel amounted to 79.08% were obtained by transesterification process with the molarratio of oil:methanol 1:10, catalyst concentration of 1%-b oil and reaction temperature of 65 ˚C for 3 hours. The CaO, Na2CO3, Ca(OH)2 and CaCO3 were found in the catalyst through the (XRD) while the basic strength of the catalyst H_ was > 9,3 determined by using Hammett Indicator phenolphthalein. The specific surface area of the catalyst obtainedthrough analysis by the (BET) method was 18.880 m2/g. Characteristics of biodiesel such as density, kinematic viscosity, acid number, and flash point have matched with the standard for biodiesel specification. Some methyl esters formed such as methyl palmitate and methyloleate were found in biodiesel through analysis of (GC-MS).Keywords : Biodiesel, catalysts, calcium oxide, activated carbon, transesterification